Recent advances in the use of Langmuir monolayers as cell membrane models - Pereira, Andressa Ribeiro; de Oliveira Junior, Osvaldo Novais (Eclética Química, 2021)
Understanding the role of biomolecules in cells at the molecular level has been the trade of Prof. Marcio Francisco Colombo and Prof. João Ruggiero Neto in their carriers, which is why it was found appropriate to address the use of Langmuir monolayers as cell membrane models in this special issue. In the review paper, we elaborate upon the reasons why Langmuir monolayers are good models with the possible control of membrane composition and molecular packing. After describing several experimental methods to characterize the Langmuir monolayers, we discuss selected results from the last five years where monolayers were made to interact with pharmaceutical drugs, emerging pollutants and other biologically-relevant molecules. The challenges to take the field forward are also commented upon.